PENGUATAN STRATEGI PEMASARAN UMKM DESA NGARGOGONDO DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT (Fakultas Ekonomi Universitas Wisnuwardhana, 2022)
This article is motivated by the phenomenon of the marketing of MSMEs in Ngargogondo Village which is not yet optimal. The not yet optimal marketing of MSMEs in Ngargogondo Village has an impact on the development of the community's economy and MSME actors have not been able to develop optimally. MSME actors must be able to design strategies to achieve effective MSME product marketing in supporting the economy. The purpose of this article is to analyze the MSME Marketing strategy in Ngargogondo Village, Borobudur District, Magelang Regency, Central Java, in order to increase MSME marketing and improve the community's economy. Data mining techniques were carried out by observation and structured interviews. The study used primary data with 20 samples of MSME actors as the object. By researching active MSMEs in Ngargogondo Village in 2022, the analytical tools used are the EFI, EFE, SWOT and MPSK Matrix. The results of the calculation of the internal and external sectors of the MSME marketing strategy of Ngargogondo Village in 2022 which are shown in the Matrix IE table are in quadrant IX which means that they are quite bad, so they are vulnerable to facing trade competition today, so they must change the marketing strategy of MSMEs in Ngargogondo Village.